2017
DOI: 10.1097/brs.0000000000001720
|View full text |Cite
|
Sign up to set email alerts
|

Internally Randomized Control Trial of Radiation Exposure Using Ultra-low Radiation Imaging Versus Traditional C-arm Fluoroscopy for Patients Undergoing Single-level Minimally Invasive Transforaminal Lumbar Interbody Fusion

Abstract: 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 23 publications
3
32
1
Order By: Relevance
“…cm 2 dose exposure. This is comparable to studies which have shown screening time of 2 minutes and 25 seconds for a percutaneous lumbar fusion (30), and another study utilising an ultra-low radiation imaging technique with 35.02 mGray (29). However, the significance of this remains unknown as there are different levels of exposure based on scatter and staff positioning.…”
Section: Radiation Exposuresupporting
confidence: 50%
See 2 more Smart Citations
“…cm 2 dose exposure. This is comparable to studies which have shown screening time of 2 minutes and 25 seconds for a percutaneous lumbar fusion (30), and another study utilising an ultra-low radiation imaging technique with 35.02 mGray (29). However, the significance of this remains unknown as there are different levels of exposure based on scatter and staff positioning.…”
Section: Radiation Exposuresupporting
confidence: 50%
“…Different imaging and navigation techniques will produce different amounts of radiation which can be a trade off with image quality. Studies have shown the use of an O-arm system, which utilises an initial 3D spin and will usually be followed by a post-operative acquisition, can produce up to 40% larger radiation dose to the patient, and compared to low dose fluoroscopy with post processing software which can reduce exposure by up to 83.5% (29,(31)(32)(33). Staff are able to leave the operating theatre during certain image acquisitions meaning the dose is directed to the patient, whereas 2D fluoroscopy will generate exposure to operating staff and surgeons as well as the patient.…”
Section: Radiation Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…The image enhancement package serves as the backbone of the standard C-arm fluoroscope and functions to enhance low-quality low-radiation images and provide the user with real-time instrument location tracking. Image enhancement of ultralow-radiation images has been described by Wang et al [10] and Nayar et al [11]. Briefly, fulldose fluoroscopic localizing images (with the Carm autoregulating pulse width and dose with the assistance of automatic brightness control) are acquired at the beginning of the procedure.…”
Section: Image Enhancementmentioning
confidence: 99%
“…In an internally randomized study [10] in which the ULRI settings were identical to those in this study, our group previously studied the use of the cumulative air kerma value displayed on the C-arm as a surrogate and found it to be highly correlated with personal dosimetry readings. In this context, it is important to recognize the overarching goal of ULRI-IE/IT, which is to acquire clin-ically safe fluoroscopic images with instrument guidance while substantially reducing radiation production.…”
Section: Limitationsmentioning
confidence: 99%